CERTAIN CONSIDERATIONS ON THE HISTORY OF SOCIO-ECONOMIC RELATIONS IN THE SOCIYETY OF THE LOWER AMUDARYA REGION (XTH CENTURY BC – FIRST HALF OF THE VITH CENTURY BC) (TAMADDUN NURI JURNALI, 2024)
In the article, fundamental changes that occurred in the early Iron Age in the area of ​​the right and left banks of Amudarya were analyzed.